Degradable bio-based polyamide composite material and preparation method thereof

By embedding the glutamate mannose Schif base monomer structure in the polyamide and using modified lignin, the problem of low degradation efficiency of existing degradable polyamide materials is solved, and high biodegradation efficiency and improved mechanical properties are achieved.

CN119798984APending Publication Date: 2025-04-11ZHONGWEI CHEM FIBER CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411999514.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing degradable polyamide materials have low degradation efficiency in the natural environment, making it difficult to achieve a biodegradation rate of 90% within six months.

Method used

The bio-based polyamide masterbatch is prepared by reaction of succinic acid, hexanediamine and glutamic acid derivative monomer, and the glutamic acid mannose Schif alkali monomer structure is embedded in the polyamide, and combined with modified lignin, forming a composite material with high biodegradation efficiency.

Benefits of technology

The biodegradation efficiency of polyamide composite materials is significantly improved, so that it reaches a degradation rate of 90% within 120 days, while improving the mechanical properties and thermal stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure BDA0005226072340000021
    Figure BDA0005226072340000021
  • Figure BDA0005226072340000091
    Figure BDA0005226072340000091
Patent Text Reader

Abstract

The invention relates to the technical field of degradable polyamide, in particular to a degradable bio-based polyamide composite material and a preparation method thereof.The degradable bio-based polyamide composite material is prepared from, by mass, 100 parts of bio-based polyamide master batch, 3-5 parts of flame retardant and 10-15 parts of modified lignin; the bio-based polyamide master batch is prepared through reaction of succinic acid, hexamethylenediamine and glutamic acid derivative monomers. The bio-based polyamide master batch is prepared through reaction of succinic acid, hexamethylenediamine and glutamic acid derivative monomers for the first time, a glutamic acid mannose Schif alkali monomer structure is embedded into a polyamide molecular chain, then a polyamide molecule contains a large number of hydroxyl side chains, the polyamide molecule is prone to moisture absorption and hydrolysis in the natural environment due to the design of polyhydroxyl, and meanwhile, the molecular weight of the polyamide master batch is reduced. Products such as glutamic acid, monosaccharide and the like obtained after hydrolysis of a polyamide molecular chain provide nutrients for growth and reproduction of microorganisms, and the biodegradation efficiency of polyamide in the natural environment is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of degradable polyamide, and in particular to a degradable bio-based polyamide composite material and a preparation method thereof. Background Art

[0002] Polyamide (nylon) is a widely used engineering plastic. It has been widely used in the automotive, electrical and electronic, textile and other industries due to its excellent mechanical properties and chemical stability. However, traditional polyamide materials are difficult to degrade in the natural environment, resulting in a large amount of polyamide waste accumulated in the environment, causing environmental pollution. Therefore, the development of various types of degradable polyamides has become one of the current research hotspots. For example, the patent with application number CN202111250911.6 discloses a degradable aromatic polyamide fiber and a preparation method thereof, and uses isophthaloyl chloride, amino acid and metaphenylenediamine as raw materials to prepare the degradable aromatic polyamide fiber; the patent with application number CN202211455835.7 discloses a high-performance degradable lignin-based nylon plastic and a preparation method and application thereof; the patent with application number CN202210284501.1 discloses a biodegradable thermoplastic polyamide elastomer and a preparation method thereof; the patent with application number CN202310476925.2 discloses a degradable polyamide polymer and a preparation method and application thereof.

[0003] However, it takes at least six months for the biodegradation rate of most existing degradable polyamides to reach over 90%, and their degradation efficiency still needs to be further improved. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a degradable bio-based polyamide composite material and a preparation method thereof. The novel polyamide composite material has high biodegradation efficiency and good mechanical properties and thermal stability.

[0005] Based on the above purpose, the present invention provides a degradable bio-based polyamide composite material, comprising the following raw materials in parts by weight: 100 parts of bio-based polyamide masterbatch, 8-12 parts of flame retardant, and 10-15 parts of modified lignin;

[0006] The bio-based polyamide masterbatch is prepared by reacting succinic acid, hexamethylenediamine, and glutamic acid derivative monomers;

[0007] The structural formula of the glutamic acid derivative monomer is as follows:

[0008]

[0009] Furthermore, the preparation method of the glutamate derivative monomer is: adding mannose to an acetate buffer, stirring and reacting at 60-80°C for 1-3h, then adding glutamate, continuing to stir and react for 12-18h, cooling to 5-10°C, filtering, and then recrystallizing with anhydrous ethanol. After centrifugation and vacuum drying, a glutamate derivative monomer is obtained, which is a Schif base monomer of glutamate mannose.

[0010] Furthermore, the dosage ratio of mannose, acetate buffer and glutamic acid is 1 g:10 mL:(0.8-0.85) g.

[0011] Furthermore, the preparation method of the bio-based polyamide masterbatch is:

[0012] A1: Add succinic acid and glutamic acid derivative monomers into deionized water, stir and dissolve at 80°C to obtain a mixed dibasic acid monomer solution;

[0013] A2: adding hexamethylenediamine to the mixed dibasic acid monomer solution, and stirring the mixture under nitrogen protection for 1-3 hours to obtain a polyamide salt solution, and then evaporating and concentrating the solution to a mass concentration of 75-85% to obtain a concentrated polyamide salt solution;

[0014] A3: After the concentrated polyamide salt solution and sodium phosphite are stirred and mixed, they are added into a reactor and reacted at 180-200°C for 2-3 hours under nitrogen protection. The temperature is then raised to 220-260°C and kept for 1-2 hours. The mixture is then evacuated to 50-70 kPa and allowed to react for 1-1.5 hours to obtain a polyamide melt. After extrusion and pelletization, a bio-based polyamide masterbatch is obtained.

[0015] Furthermore, the raw materials for preparing the bio-based polyamide masterbatch include, by weight, 82-88 parts of succinic acid, 30-45 parts of glutamic acid derivative monomers, 230-350 parts of deionized water, 100 parts of hexamethylenediamine, and 1-2 parts of sodium phosphite.

[0016] Furthermore, the flame retardant includes one or more of diethylphosphinate, melamine polyphosphate, tributyl phosphate, magnesium hydroxide, and zinc borate.

[0017] Furthermore, the preparation method of the modified lignin is as follows: adding lignin fiber to a 1M hydrochloric acid solution, stirring and swelling the fiber at 50-60°C for 2-3h, filtering, washing, and drying the fiber, adding the fiber to anhydrous acetone, stirring the fiber thoroughly, adding itaconic acid and p-toluenesulfonic acid, refluxing the fiber at 60°C and stirring the fiber for 3-5h, and then removing the acetone solvent by rotary evaporation. The fiber is then washed, filtered, and vacuum dried to obtain the modified lignin.

[0018] Furthermore, the usage ratio of the lignin fiber, 1M hydrochloric acid solution, anhydrous acetone, itaconic acid and p-toluenesulfonic acid is 1 g:10 mL:20 mL:(0.2-0.4) g:(0.02-0.03) g.

[0019] The present invention further provides a method for preparing the biodegradable bio-based polyamide composite material, comprising the following steps: uniformly mixing a bio-based polyamide masterbatch, a flame retardant and modified lignin, extruding and granulating the mixture through a twin-screw extruder to obtain the biodegradable bio-based polyamide composite material.

[0020] Beneficial effects of the present invention:

[0021] The present invention prepares a bio-based polyamide masterbatch for the first time by reacting succinic acid, hexamethylenediamine and glutamic acid derivative monomers, so that a glutamic acid mannose Schif base monomer structure is embedded in the polyamide molecular chain, thereby making the polyamide molecule contain a large number of hydroxyl side chains. The multi-hydroxyl design makes it easy to absorb moisture and hydrolyze in a natural environment. At the same time, the products of the hydrolysis of the polyamide molecular chain, such as glutamic acid and monosaccharides, provide nutrients for the growth and reproduction of microorganisms, further accelerating the biodegradation efficiency of the polyamide in a natural environment.

[0022] At the same time, the Schif base monomer of glutamate mannose synergizes with the modified lignin in the polyamide system, and acts synergistically with the modified lignin to further improve the biodegradability of polyamide, and to a certain extent also helps to improve the mechanical properties of polyamide composites. DETAILED DESCRIPTION

[0023] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0024] Example 1

[0025] A method for preparing a biodegradable bio-based polyamide composite material comprises the following steps:

[0026] S1: Preparation of glutamic acid derivative monomer: adding mannose to acetate buffer, stirring and reacting at 60°C for 1.5h, then adding glutamic acid, continuing to stir and react for 12h, cooling to 5°C, filtering, and then recrystallizing with anhydrous ethanol, centrifuging, and vacuum drying to obtain a glutamic acid derivative monomer, which is a Schif base monomer of glutamic acid mannose;

[0027] The dosage ratio of mannose, acetate buffer and glutamic acid is 1 g:10 mL:0.8 g;

[0028] S2: Preparation of bio-based polyamide masterbatch:

[0029] S201: Prepare the following materials in parts by weight: 88 parts of succinic acid, 30 parts of glutamic acid derivative monomer, 230 parts of deionized water, 100 parts of hexamethylenediamine, and 1 part of sodium phosphite;

[0030] S202: adding succinic acid and glutamic acid derivative monomers into deionized water, stirring and dissolving at 80° C. to obtain a mixed dibasic acid monomer solution;

[0031] S203: adding hexamethylenediamine to the mixed dibasic acid monomer solution, and stirring the mixture under nitrogen protection for 1.5 hours to obtain a polyamide salt solution, and then evaporating and concentrating the solution to a mass concentration of 75% to obtain a concentrated polyamide salt solution;

[0032] S204: After the concentrated polyamide salt solution and sodium phosphite are stirred and mixed, they are added into a reactor, and reacted at 180° C. for 2 h under nitrogen protection, and then the temperature is raised to 220° C. and kept for 1 h, and then vacuumed to 50 kPa, and the reaction is continued for 1 h to obtain a polyamide melt, which is extruded and pelletized to obtain a bio-based polyamide masterbatch;

[0033] S3: preparing the modified lignin: adding lignin fiber to a 1M hydrochloric acid solution, stirring and swelling at 50°C for 2h, filtering, washing, and drying, adding to anhydrous acetone, stirring sufficiently, adding itaconic acid and p-toluenesulfonic acid, refluxing and stirring at 60°C for 3h, and then rotary evaporating to remove the acetone solvent, washing, filtering, and vacuum drying to obtain modified lignin;

[0034] The usage ratio of the lignin fiber, 1M hydrochloric acid solution, anhydrous acetone, itaconic acid, and p-toluenesulfonic acid is 1g:10mL:20mL:0.2g:0.02g;

[0035] S4: Preparation of biodegradable bio-based polyamide composite materials: 100 parts of bio-based polyamide masterbatch, 8 parts of flame retardant diethyl phosphinate and 10 parts of modified lignin are mixed uniformly by mass, and then extruded and granulated through a twin-screw extruder. The working temperature of each zone of the twin-screw extruder is: 235°C in zone 1, 240°C in zone 2, 250°C in zone 3, and 255°C in zone 4. The screw speed is 400rpm to obtain a biodegradable bio-based polyamide composite material.

[0036] Example 2

[0037] A method for preparing a biodegradable bio-based polyamide composite material comprises the following steps:

[0038] S1: Preparation of glutamic acid derivative monomer: adding mannose to acetate buffer, stirring and reacting at 70°C for 1-3h, then adding glutamic acid, continuing to stir and react for 15h, cooling to 8°C, filtering, and then recrystallizing with anhydrous ethanol, centrifuging, and vacuum drying to obtain a glutamic acid derivative monomer, which is a Schif base monomer of glutamic acid mannose;

[0039] The dosage ratio of mannose, acetate buffer and glutamic acid is 1 g:10 mL:0.82 g;

[0040] S2: Preparation of bio-based polyamide masterbatch:

[0041] S201: Prepare the following materials in parts by weight: 85 parts of succinic acid, 37.5 parts of glutamic acid derivative monomer, 280 parts of deionized water, 100 parts of hexamethylenediamine, and 1.5 parts of sodium phosphite;

[0042] S202: adding succinic acid and glutamic acid derivative monomers into deionized water, stirring and dissolving at 80° C. to obtain a mixed dibasic acid monomer solution;

[0043] S203: adding hexamethylenediamine to the mixed dibasic acid monomer solution, and stirring the mixture for 1-3 hours under nitrogen protection to obtain a polyamide salt solution, and then evaporating and concentrating the solution to a mass concentration of 80% to obtain a concentrated polyamide salt solution;

[0044] S204: The concentrated polyamide salt solution and sodium phosphite are stirred and mixed, and then added into a reactor, and reacted at 190° C. for 2.5 hours under nitrogen protection, and then heated to 240° C. and kept warm for 1.5 hours, and then evacuated to 60 kPa, and continued to stand for 1.5 hours to obtain a polyamide melt, which was extruded and pelletized to obtain a bio-based polyamide masterbatch;

[0045] S3: preparing the modified lignin: adding lignin fiber to a 1M hydrochloric acid solution, and stirring and swelling the fiber at 55°C for 2.5 hours, filtering, washing, and drying, and then adding the fiber to anhydrous acetone, stirring the fiber thoroughly, adding itaconic acid and p-toluenesulfonic acid, and stirring the fiber under reflux at 60°C for 4 hours, and then removing the acetone solvent by rotary evaporation, washing, filtering, and vacuum drying to obtain the modified lignin;

[0046] The usage ratio of the lignin fiber, 1M hydrochloric acid solution, anhydrous acetone, itaconic acid, and p-toluenesulfonic acid is 1g:10mL:20mL:0.3g:0.025g;

[0047] S4: Preparation of biodegradable bio-based polyamide composite materials: 100 parts of bio-based polyamide masterbatch, 10 parts of flame retardant melamine polyphosphate and 12.5 parts of modified lignin are mixed uniformly by mass, and then extruded and granulated through a twin-screw extruder. The working temperatures of each zone of the twin-screw extruder are: 235°C in zone 1, 240°C in zone 2, 250°C in zone 3, and 255°C in zone 4. The screw speed is 400rpm to obtain a biodegradable bio-based polyamide composite material.

[0048] Example 3

[0049] A method for preparing a biodegradable bio-based polyamide composite material comprises the following steps:

[0050] S1: Preparation of glutamic acid derivative monomer: adding mannose to acetate buffer, stirring and reacting at 80°C for 3h, then adding glutamic acid, continuing to stir and react for 18h, cooling to 10°C, filtering, and then recrystallizing with anhydrous ethanol, centrifuging, and vacuum drying to obtain a glutamic acid derivative monomer, which is a Schif base monomer of glutamic acid mannose;

[0051] The dosage ratio of mannose, acetate buffer and glutamic acid is 1 g:10 mL:0.85 g;

[0052] S2: Preparation of bio-based polyamide masterbatch:

[0053] S201: Prepare the following materials in parts by weight: 82 parts of succinic acid, 45 parts of glutamic acid derivative monomer, 350 parts of deionized water, 100 parts of hexamethylenediamine, and 2 parts of sodium phosphite;

[0054] S202: adding succinic acid and glutamic acid derivative monomers into deionized water, stirring and dissolving at 80° C. to obtain a mixed dibasic acid monomer solution;

[0055] S203: adding hexamethylenediamine to the mixed dibasic acid monomer solution, and stirring the mixture under nitrogen protection for 3 hours to obtain a polyamide salt solution, and then evaporating and concentrating the mixture to a mass concentration of 85% to obtain a concentrated polyamide salt solution;

[0056] S204: After the concentrated polyamide salt solution and sodium phosphite are stirred and mixed, they are added into a reactor, and reacted at 200° C. for 3 h under nitrogen protection, and then the temperature is raised to 260° C. and kept for 2 h, and then evacuated to 70 kPa, and the reaction is continued for 1.5 h to obtain a polyamide melt, which is extruded and pelletized to obtain a bio-based polyamide masterbatch;

[0057] S3: preparing the modified lignin: adding lignin fiber to a 1M hydrochloric acid solution, stirring and swelling at 60°C for 3h, filtering, washing, and drying, adding to anhydrous acetone, stirring sufficiently, adding itaconic acid and p-toluenesulfonic acid, refluxing and stirring at 60°C for 3-5h, and then rotary evaporating to remove the acetone solvent, washing, filtering, and vacuum drying to obtain modified lignin;

[0058] The usage ratio of the lignin fiber, 1M hydrochloric acid solution, anhydrous acetone, itaconic acid, and p-toluenesulfonic acid is 1g:10mL:20mL:0.4g:0.03g;

[0059] S4: Preparation of biodegradable bio-based polyamide composite materials: 100 parts of bio-based polyamide masterbatch, 10 parts of flame retardant tributyl phosphate and 15 parts of modified lignin are mixed uniformly by mass, and then extruded and granulated through a twin-screw extruder. The working temperatures of each zone of the twin-screw extruder are: 235°C in zone 1, 240°C in zone 2, 250°C in zone 3, and 255°C in zone 4. The screw speed is 400rpm to obtain a biodegradable bio-based polyamide composite material.

[0060] Comparative Example 1 is the same as Example 1, except that no glutamic acid derivative monomer is added during the preparation of the bio-based polyamide masterbatch. The preparation method is as follows:

[0061] Prepare the materials according to the following mass parts: 100 parts of succinic acid, 230 parts of deionized water, 100 parts of hexamethylenediamine, and 1 part of sodium phosphite; the molar ratio of hexamethylenediamine to succinic acid is about 1:1 (the amount of hexamethylenediamine is slightly higher than that of succinic acid);

[0062] Add succinic acid into deionized water, stir and dissolve at 80°C to obtain a succinic acid solution;

[0063] Add hexamethylenediamine to the succinic acid solution, and react under nitrogen protection with stirring for 1.5 hours to obtain a polyamide salt solution, and then evaporate and concentrate to a mass concentration of the salt solution of 75% to obtain a concentrated polyamide salt solution;

[0064] The concentrated polyamide salt solution and sodium phosphite are stirred and mixed, then added into a reactor, and reacted at 180°C for 2 hours under nitrogen protection, then heated to 220°C and kept warm for 1 hour, then evacuated to 50 kPa, and allowed to react for 1 hour to obtain a polyamide melt. After extrusion and pelletization, a bio-based polyamide masterbatch is obtained.

[0065] Comparative Example 2 is the same as Example 1, except that no modified lignin is added during the preparation of the polyamide composite material.

[0066] Degradation performance test of biodegradable bio-based polyamide composite materials: Referring to the standard of GB / T19277-2003, the final aerobic biodegradability of PBAT polyester masterbatch under controlled industrial composting conditions was determined. Under industrial aerobic composting conditions of 55°C, 500g of culture soil and 100g of bio-based polyamide composite materials were placed in a degradation reaction vessel as the experimental group to determine the final aerobic biodegradability of the composite materials. The blank control group was used without adding bio-based polyamide composite materials. The amount of CO2 produced in the reaction vessel was determined by an infrared online gas analysis system.

[0067] The tensile strength of the degradable bio-based polyamide composite materials prepared in Examples 1-3 and Comparative Examples 1-2 was measured according to ASTM-D638 standard.

[0068] The biodegradability and mechanical properties of the polyamide composite materials prepared in the examples and comparative examples are shown in Table 1:

[0069] Table 1

[0070]

[0071] As shown in Table 1, the degradation rate of the bio-based polyamide composites prepared in Examples 1-3 can reach more than 90% at the 120th day, and the biodegradation rates of Comparative Examples 1 and 2 are significantly lower than that of Example 1, indicating that the biodegradation effect of the polyamide composite can be effectively accelerated by inserting the glutamic acid mannose Schif base monomer structure into the polyamide molecule, and the addition of modified lignin to the polyamide system also helps to improve its biodegradation effect. At the same time, under the synergistic effect of the glutamic acid mannose Schif base monomer and the modified lignin, it also helps to improve the mechanical properties of the polyamide composite to a certain extent.

[0072] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention (including the claims) is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0073] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A biodegradable bio-based polyamide composite material, characterized in that: The invention comprises the following raw materials by weight: 100 parts of bio-based polyamide masterbatch, 3-5 parts of flame retardant, and 10-15 parts of modified lignin; The bio-based polyamide masterbatch is prepared by reacting succinic acid, hexamethylenediamine, and glutamic acid derivative monomers; The structural formula of the glutamic acid derivative monomer is as follows:

2. The biodegradable bio-based polyamide composite material according to claim 1, characterized in that: The preparation method of the glutamic acid derivative monomer is as follows: adding mannose to an acetate buffer, stirring and reacting at 60-80° C. for 1-3 hours, then adding glutamic acid, continuing to stir and react for 12-18 hours, cooling to 5-10° C., filtering, and then recrystallizing with anhydrous ethanol, centrifuging, and vacuum drying to obtain the glutamic acid derivative monomer.

3. The biodegradable bio-based polyamide composite material according to claim 2, characterized in that: The dosage ratio of mannose, acetate buffer and glutamic acid is 1 g:10 mL:(0.8-0.85) g.

4. A degradable bio-based polyamide composite material according to any one of claims 1 to 3, characterized in that: The preparation method of the bio-based polyamide masterbatch is: A1: Add succinic acid and glutamic acid derivative monomers into deionized water, stir and dissolve at 80°C to obtain a mixed dibasic acid monomer solution; A2: adding hexamethylenediamine to the mixed dibasic acid monomer solution, and stirring the mixture under nitrogen protection for 1-3 hours to obtain a polyamide salt solution, and then evaporating and concentrating the solution to a mass concentration of 75-85% to obtain a concentrated polyamide salt solution; A3: After the concentrated polyamide salt solution and sodium phosphite are stirred and mixed, they are added into a reactor and reacted at 180-200°C for 2-3 hours under nitrogen protection. The temperature is then raised to 220-260°C and kept for 1-2 hours. The mixture is then evacuated to 50-70 kPa and allowed to react for 1-1.5 hours to obtain a polyamide melt. After extrusion and pelletization, a bio-based polyamide masterbatch is obtained.

5. The biodegradable bio-based polyamide composite material according to claim 4, characterized in that: The raw materials for preparing the bio-based polyamide masterbatch include, by weight, 82-88 parts of succinic acid, 30-45 parts of glutamic acid derivative monomers, 230-350 parts of deionized water, 100 parts of hexamethylenediamine, and 1-2 parts of sodium phosphite.

6. The biodegradable bio-based polyamide composite material according to claim 1, characterized in that: The flame retardant includes one or more of diethylphosphinate, melamine polyphosphate, tributyl phosphate, magnesium hydroxide and zinc borate.

7. The biodegradable bio-based polyamide composite material according to claim 1, characterized in that: The preparation method of the modified lignin is as follows: adding lignin fiber to a 1M hydrochloric acid solution, stirring and swelling at 50-60°C for 2-3h, filtering, washing, and drying, adding to anhydrous acetone, stirring sufficiently, adding itaconic acid and p-toluenesulfonic acid, refluxing at 60°C and stirring for 3-5h, and then rotary evaporating to remove the acetone solvent, washing, filtering, and vacuum drying to obtain the modified lignin.

8. The biodegradable bio-based polyamide composite material according to claim 1, characterized in that: The dosage ratio of the lignin fiber, 1M hydrochloric acid solution, anhydrous acetone, itaconic acid and p-toluenesulfonic acid is 1g:10mL:20mL:(0.2-0.4)g:(0.02-0.03)g.

9. A method for preparing a degradable bio-based polyamide composite material according to any one of claims 1-3 and 5-8, characterized in that: The following steps are involved: The bio-based polyamide masterbatch, flame retardant and modified lignin are uniformly mixed, extruded and granulated through a twin-screw extruder to obtain a degradable bio-based polyamide composite material.

Citation Information

Patent Citations

  • Degradable aromatic polyamide fiber and preparation method thereof

    CN113981559A

  • Biodegradable thermoplastic polyamide elastomer and preparation method thereof

    CN114644754A

  • A high-performance biodegradable lignin-based nylon plastic and its preparation method and application

    CN115725173B

  • Degradable polyamide polymer as well as preparation method and application thereof

    CN116284755A